2015
DOI: 10.1186/s12985-015-0260-1
|View full text |Cite
|
Sign up to set email alerts
|

Healthy rabbits are susceptible to Epstein-Barr virus infection and infected cells proliferate in immunosuppressed animals

Abstract: BackgroundEpstein-Barr virus (EBV) is an oncogenic virus implicated in the pathogenesis of several human malignancies. However, due to the lack of a suitable animal model, a number of fundamental questions pertaining to the biology of EBV remain poorly understood. Here, we explore the potential of rabbits as a model for EBV infection and investigate the impact of immunosuppression on viral proliferation and gene expression.MethodsSix healthy New Zealand white rabbits were inoculated intravenously with EBV and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(47 citation statements)
references
References 66 publications
3
44
0
Order By: Relevance
“…Rabbits have been also used to recapitulate features of EBV infection in humans [6]. Intravenous inoculation of EBV to New Zealand White rabbits followed by immunosuppression with cyclosporine A induced proliferation of EBV-positive lymphoblasts with the latency III type of viral gene expression in the spleen and the liver, indicating the possibility of using rabbits as a model of EBV-associated LPD [17]. The lineage (B or T) of EBV-infected lymphoblasts was not identified in this study.…”
Section: Ebv-positive Lpd In Laboratory Animals Induced By Experimentmentioning
confidence: 99%
“…Rabbits have been also used to recapitulate features of EBV infection in humans [6]. Intravenous inoculation of EBV to New Zealand White rabbits followed by immunosuppression with cyclosporine A induced proliferation of EBV-positive lymphoblasts with the latency III type of viral gene expression in the spleen and the liver, indicating the possibility of using rabbits as a model of EBV-associated LPD [17]. The lineage (B or T) of EBV-infected lymphoblasts was not identified in this study.…”
Section: Ebv-positive Lpd In Laboratory Animals Induced By Experimentmentioning
confidence: 99%
“…Ten tree shrews were inoculated with EBV by intravenous injection of 500μl of the viral solution described previously. The EBV copy number in the inoculums was approximately 3.9 × 10 8 copies per animal as confirmed by real-time quantitative PCR(qPCR).The infectivity of the virus in the viral solution was assessed by its ability to successfully immortalize human PBMCs in vitro [ 25 , 58 ]. The10 tree shrews inoculated with EBV were designated Ts1-Ts10.…”
Section: Methodsmentioning
confidence: 99%
“…Studies of EBV using transgenic animal models have focused on individual genes such as EBNA1 and LMP1 [ 20 22 ]. Recent studies have confirmed that rabbits can be infected with EBV via venous and nasal inoculation [ 23 25 ] and that EBV can infect rabbit B cells in vitro [ 26 ]. Although these animal models have played important roles in studying the EBV infection process, its pathogenic mechanism, and its prevention and treatment, they also present some disadvantages.…”
Section: Introductionmentioning
confidence: 99%
“…Sections were counterstained with haematoxylin, dehydrated and mounted for microscopic analysis. Formalin-fixed paraffin embedded sections from an EBV infected rabbit spleen [ 33 ] were included as a positive control.…”
Section: Methodsmentioning
confidence: 99%